Activity of disinfectants related to food hygiene and sanitation - Lima, Farzana Rahman; Ahmed, Shahabuddin (Northern International Medical College Journal, 2015)
Objectives : To observe the activity of disinfectants related to food hygiene and sanitation and to determine the germicidal effect of those disinfectants against various microorganisms adhered to different surface materials in relation with time and concentration. Materials and Methods : The study was carried out in the Institute of Nutrition and Food Science (INFS) of Dhaka University, Dhaka during FebruarySeptember 2002. The disinfectants were sodium hypochlorite (NaOC1) and calcium hypochlorite Ca(OCl)2. Minimum Inhibitory Concentration (MIC), Qualitative and Quantitative suspension test, Phenolic co-efficient test and Germicidal effect of NaOC1 and Ca (OCI)2 against E coli and Staph aureus on different surface materials were tested. Surface materials of the experiment were 4 sq cm of wood, tin, rexene, formica and ceramic tile pieces. Results : The disinfectants related to food hygiene and sanitation was studied critically. The concentration of 2% and 8% for Ca(OC1)2 and NaOCl respectively would be ideal. Gram negative bacteria (E coli) was more sensitive to NaOCl than gram positive bacteria (Staph aureus) and gram positive bacteria was more sensitive to Ca(OC1)2 than gram negative bacteria on all the five surface materials.. The Germicidal effect of Ca(OC1)2 was found better than that of NaOC1. Conclusion : Considering the result it can be concluded that both the hypochlorite are more active and effective disinfectant against E coli and Staph aureus. Therefore, to prepare the wholesome and safe food Ca(OC1)2 and NaOC1 are considered as ideal disinfectant for rendering food preparing places and sites free from contamination. Northern International Medical College Journal Vol.6(2) 2015: 64-67